2021
DOI: 10.4236/jhrss.2021.93028
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Workload, Job Satisfaction, Work Stress and Organizational Commitment on Turnover Intention: Evidence from Hospitality Management Educators

Abstract: This study was conducted to describe and measure the factors influencing faculty members' workload, job satisfaction, work stress, organizational commitment, and turnover intentions in hospitality education. To achieve this goal, 400 hospitality management educators of both public and private tertiary educational systems in NCR were selected through purposive-quota sampling. A semi-structured questionnaire and focus group discussion were used to collect data from the participants. Descriptive statistics includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…It is influenced by job satisfaction, including fulfillment in teaching, positive relationships, and supportive leadership, as well as the work environment, growth opportunities, and recognition (Lantican, 2021).…”
Section: Framework Of the Studymentioning
confidence: 99%
“…It is influenced by job satisfaction, including fulfillment in teaching, positive relationships, and supportive leadership, as well as the work environment, growth opportunities, and recognition (Lantican, 2021).…”
Section: Framework Of the Studymentioning
confidence: 99%
“…Organizational commitment is about the work-related attitude, which is quite crucial to the study of career or work behavior such as withdrawal (Greenhaus and Parasuraman, 1986). It was proven that organizational commitment and job satisfaction, have a significant direct effect on turnover intention (Lantican, 2021). There are varying classifications of organizational commitment dimensions in the relevant studies.…”
Section: Organisational Commitmentmentioning
confidence: 99%
“…Employee turnover has been a significant managerial problem in Indonesia (Karinadewi & Martdianty, 2020). Several studies have described the relationship between job stress (Lantican, 2021;Park & Min, 2020;Rehman & Mubashar, 2017), job insecurity (Brahmannanda & Dewi, 2020;Bajrami et al, 2021), and compensation (Brahmannanda & Dewi, 2020;Saputra & Suwandana, 2021;Vizano et al, 2021) on turnover intention. A high turnover intention can result in financial losses for the company because it takes time for new employees to get to know the company's culture and environment and the costs for training (Saputra & Suwandana, 2021).…”
Section: Literature Review Turnover Intentionmentioning
confidence: 99%
“…Finding the primary causes of hospitality workers leaving their jobs in large numbers is challenging. Previous studies indicated that the reason for hotel employee turnover is poor pay and advantages (Che Ahmat et al, 2019;Jolly et al, 2021), job stress (Chen et al, 2022;Rehman & Mubashar, 2017), job insecurity (Asimah, 2018;Bajrami et al, 2021;Dusek et al, 2016), compensation (Atongdem & Combert, 2019;Okae, 2018;Santhanam et al, 2017), and several things such as working hours, workload, work pressure, training and development, leadership, career plans, and family factors (Aynalem et al, 2016;Blomme et al, 2010;Gom et al, 2021;Lantican, 2021;Mensah et al, 2021;Mooney, 2019;Wang et al, 2017). Dwesini (2019) conducted a literature review in 2019 which found that researchers have empirically studied the issue of industrial labor turnover in several countries, including South Africa, Australia, Greece, and the United States.…”
Section: Introductionmentioning
confidence: 99%